Climate Governance and the Future of Smallholder Agriculture Under Increasing Environmental Uncertainty in Zimbabwe - Shingirai Mugambiwa; Frank Rapholo (CV. Literasi Indonesia, 2025)
This paper investigates the intersection of climate governance and the resilience of smallholder agriculture under conditions of increasing environmental uncertainty. The study employed a qualitative methodology. Data were acquired through semi-structured interviews, focus group discussions, and documentary scrutiny of relevant policy texts. The sample comprised thirty (30) participants consisting of farmers, agricultural extension officers, and representatives of non-governmental organizations in the Mutoko district of Zimbabwe. Thematic Analysis was employed to analyse data. The findings of the study revealed systematic divergences between policy aspirations and grassroots implementation, particularly in domains of land tenure security, equitable allocation of agricultural inputs, and the inclusivity of support schemes. The study also established that governance instruments remain predominantly prescriptive and centralized, effectively blocking the experiential contributions of women, youth, and economically marginal farmers, all of whom shoulder disproportionate climatic risk and live on the edges of subsistence.